2018
DOI: 10.3389/fneur.2018.00614
|View full text |Cite
|
Sign up to set email alerts
|

Combinatory Biomarker Use of Cortical Thickness, MUNIX, and ALSFRS-R at Baseline and in Longitudinal Courses of Individual Patients With Amyotrophic Lateral Sclerosis

Abstract: Objective: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative process affecting upper and lower motor neurons as well as non-motor systems. In this study, precentral and postcentral cortical thinning detected by structural magnetic resonance imaging (MRI) were combined with clinical (ALS-specific functional rating scale revised, ALSFRS-R) and neurophysiological (motor unit number index, MUNIX) biomarkers in both cross-sectional and longitudinal analyses.Methods: The unicenter sample include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
(112 reference statements)
2
14
0
Order By: Relevance
“…MUNE was positively correlated with the MRC score and the clinical dysfunction measured by the ALSFRS-R scale. This finding was in agreement with other researchers, although using MUNIX instead of MUNE as a measure [23,24]. MUNE is calculated by dividing the maximal CMAP amplitude by the mean surface SMUP [25].…”
Section: Discussionsupporting
confidence: 92%
“…MUNE was positively correlated with the MRC score and the clinical dysfunction measured by the ALSFRS-R scale. This finding was in agreement with other researchers, although using MUNIX instead of MUNE as a measure [23,24]. MUNE is calculated by dividing the maximal CMAP amplitude by the mean surface SMUP [25].…”
Section: Discussionsupporting
confidence: 92%
“…Because ALS is a clinically heterogeneous condition with considerable variation in survival times, accurate prognostic indicators are urgently needed . We showed that the simulated aggregation levels based on early imaging data can help to predict survival of individual patients in a large dataset of ALS patients.…”
Section: Discussionmentioning
confidence: 98%
“…Possible direct effects of G-CSF upon the CNS were not assessed, as we did not obtain post-mortem analysis of deceased patients. Neuroimaging studies conducted on our G-CSF treated patient cohort ( 77 ) did not directly address possible G-CSF related structural effects—we also had no patient control group without G-CSF treatment. One indirect mode of action by which G-CSF exerts neuroprotective effects may be through polarization of the immune system toward an anti-inflammatory state ( 13 ).…”
Section: Discussionmentioning
confidence: 99%